Lactobacillus Modulates Chlamydia Infectivity and Genital Tract Pathology in vitro and in vivo - Chen, Hongliang; Min, Shuling; Wang, Li; Zhao, Lanhua; Luo, Fangzhen; Lei, Wenbo; Wen, Yating; Luo, Lipei; Zhou, Qianting; Peng, Lixiu; Li, Zhongyu (Frontiers in Microbiology, 2022)
Since we previously reported that women infected with chlamydia had a significant overall reduction in Lactobacillus in the vagina microbiota as compared to those uninfected individuals; the interactions between the altered Lactobacillus and Chlamydia trachomatis, on the other hand, need to be elucidated. Here, we employed both in vitro and in vivo models to evaluate the effects of this changed Lactobacillus on Chlamydia infection. We found that L. iners, L. crispatus, L. jensenii, L. salivarius, L. gasseri, L. mucosae, and L. reuteri all significantly reduced C. trachomatis infection in a dose- and time-dependent manner. The strongest anti-Chlamydia effects were found in L. crispatus (90 percent reduction), whereas the poorest was found in L. iners (50 percent reduction). D (–) lactic acid was the key component in Lactobacillus cell-free supernatants (CFS) to inactivate Chlamydia EBs, showing a positive correlation with the anti-Chlamydia activity. The effects of D (–) lactic acid were substantially attenuated by neutralizing the pH value to 7.0. In vivo, mice intravaginally inoculated with Lactobacillus mixtures (L. crispatus, L. reuteri, and L. iners at a ratio of 1:1:1), but not single Lactobacillus, after genital Chlamydia infection, significantly attenuated the levels of Chlamydia live organism shedding in both the lower genital tract and the intestinal tract, reduced cytokines production (TNF-α, IFN-γ, and IL-1β) in the vagina, and lessened upper genital tract inflammation and pathogenicity. Taken together, these data demonstrate that Lactobacillus inhibits Chlamydia infectivity both in vivo and in vitro, providing useful information for the development of Lactobacillus as adjunctive treatment in Chlamydia infection.